Modular functions of one Variable VI : proceedings international conference, University of Bonn, Sonderforschungs-beereich Theoretische Mathematik July 2-14, 1976 - Serre, Jean-Pierre; Zagier, D. B. (Berlin : Springer-Verlag, 1972)
Vols. 1-4: proceedings of the International Summer School, University of Antwerp, July 17-August 3, 1972
Vols. 5- : proceedings of the International Conference, University of Bonn, Sonderforschungsbereich Theoretische Mathematik, July 2-14, 1976.
Includes bibliographies and index
engfre
1
Keywords: Functions, Modular -- Congresses; Algebraic number theory -- Congresses